Comment on “Artificial intelligence to predict oncological outcome directly from hematoxylin and eosin-stained slides in urology: da systematic review” - Rivero Belenchón, Inés; Checcucci, Enrico; Gomez Rivas, Juan; Puliatti, Stefano; Taratkin, Mark; Kowalewski, Karl-Friedrich; Rodler, Severin; Veccia, Alessandro; Medina Lopez, Rafael A.; Cacciamani, Giovanni (Minerva urology and nephrology, 2022)
Comment on “Artificial intelligence to predict oncological outcome directly from hematoxylin and eosin-stained slides in urology: a systematic review”